2010
DOI: 10.1673/031.010.10601
|View full text |Cite
|
Sign up to set email alerts
|

Life History Parameters of the Sunn Pest,Eurygaster integriceps, Held at Four Constant Temperatures

Abstract: The Sunn-pest, Eurygaster integriceps Puton (Heteroptera: Scutelleridae), is the most important insect pest of wheat and barley in Iran. A demographic study was carried out in order to determine the effect of temperature on life history parameters of the pest. Life tables were constructed at four constant temperatures: 22, 25, 27, and 30 ± 1° C using Mahdavi wheat kernels as food. Finite and intrinsic rates of population increase, gross and net reproductive rates, intrinsic rates of birth and death, generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…In both years, during the period considered above, the average maximum temperature was highest in Zone 2, whereas Zone 1 always presented the lowest average minimum temperature. Higher temperatures stimulate the development of wheat bugs (Javahery 1996; Iranipour et al 2010) and could explain the different densities in the three zones (Figure 4). …”
Section: Resultsmentioning
confidence: 99%
“…In both years, during the period considered above, the average maximum temperature was highest in Zone 2, whereas Zone 1 always presented the lowest average minimum temperature. Higher temperatures stimulate the development of wheat bugs (Javahery 1996; Iranipour et al 2010) and could explain the different densities in the three zones (Figure 4). …”
Section: Resultsmentioning
confidence: 99%
“…The PDD value was obtained for different stages of the sunn pest using the following formula: PDD = t(c − a), where t is the general range of generation time and c and a are the ranges of practical and theoretical temperatures respectively. 58 According to Iranipour et al, 57 the generation time periods ranged from 121 to 40 days when the temperature dropped from 22 to 30 ∘ C. In addition, Mozaffari and Azizian 59 indicated that sunn pest degree-days range between 413.8 and 1132. Accordingly, the selected value of 1180 degree-days was set to exclude cold Northern Hemisphere countries and to limit pests in Europe.…”
Section: Annual Heat Summentioning
confidence: 99%
“…By using the above said observations life and fecundity tables were constructed for BPH at different temperature regimes. The methodology followed in the present investigation was adopted from Iranipour et al (2010).…”
Section: Observationsmentioning
confidence: 99%